(untitled) (Conference Series, 2022)
The world of Christianity in Indonesia has a complicated history and culture. The Indian sub-continent, Arab and Chinese traders, European colonialism, and American interests have influenced the indigenous culture over centuries and developed complicated relationships within the country. This complex mixture makes Indonesia unique to the rest of Southeast Asia—possibly the rest of the world—and raises challenges to spreading the gospel. Indonesian Christian denominations face those challenges when encountering the gospel with different cultures around Indonesia. There is a constant tension of assimilation between local culture and the gospel. This tension pressures pastors to take compromising actions at a level that is sometimes dangerous because they have crossed the boundaries of contextualization and are trapped in syncretism.